2019
DOI: 10.18203/2320-1770.ijrcog20190499
|View full text |Cite
|
Sign up to set email alerts
|

Painless labour: attitude and awareness amongst pregnant women

Abstract: Background: Labour pain has been described as most severe pain experienced by a female. Labour analgesia is widely practiced in developed countries. Many labour analgesic methods have been introduced to make delivery a pleasurable moment in a women’s life.Methods: This prospective study was performed at the Department of Obstetrics and Gynaecology, Indira Gandhi Institute of Medical Sciences, Patna, India after getting permission from institute ethical committee. 100 pregnant females attending the antenatal cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Regarding the relationship between the total scores of knowledge and the total scores of attitudes regarding painless labor among the studied pregnant women, a significant relationship was found between the total score of knowledge and the total score of attitudes regarding painless labor among the studied pregnant women. This result is consistent with Sinha A et al, (2019) (37) and Delwatta S et al, (2019) (26) findings. Also, Zaihi Z et al, (2020) (56) found that there was a relationship between knowledge and attitudes of pregnant women regarding epidural anesthesia.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Regarding the relationship between the total scores of knowledge and the total scores of attitudes regarding painless labor among the studied pregnant women, a significant relationship was found between the total score of knowledge and the total score of attitudes regarding painless labor among the studied pregnant women. This result is consistent with Sinha A et al, (2019) (37) and Delwatta S et al, (2019) (26) findings. Also, Zaihi Z et al, (2020) (56) found that there was a relationship between knowledge and attitudes of pregnant women regarding epidural anesthesia.…”
Section: Discussionsupporting
confidence: 92%
“…Concerning the studied pregnant women's educational level, more than half of them had university education. This finding matches with Paul D et al, (2022) (35) , Alahmari S et al, (2020) (36) and Sinha A et al, (2019) (37) findings. While, this finding is dissimilar to Abd El-Salam A et al, (2022) (38) and Abo El-nassr A et al, (2022) (32) who showed that less than two-thirds of the women in their study had secondary education.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations